A comparative study on the performances of layer hybrids in some selected areas of Khulna region - Islam, SS; Paul, C; Sarker, BC (Bangladesh Journal of Animal Science, 2013)
<!–[if gte mso 9]> <![endif]–><span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">A survey was conducted in Batiaghata and Dacope upazilla of Khula district during the period from August to October, 2013 to observe the socioeconomic conditions of poultry farmers, existing feeding and management practices of poultry farms and performances of 5 different layer hybrids. The commercial layer hybrids considered in present study were of 30 layer farmers selected randomly from each Upazilla to collect the information. Data were collected using a pretested questionnaire by direct interview of the farmers. Collected data were analyzed using SPSS. To observe the socioeconomic conditions, the age of selected farmers, their occupation, education level, family size, land size and annual income were considered. Mean age at first lay did not vary significantly among 5 different hybrids. Average mature weights of layer birds varied significantly (P<0.001) among 5 hybrids. Average egg production percentage was highest in Hisex White (86.81±1.86) and lowest in Decalb White (59.75±14.81). Average egg weight (g/egg) was highest in ISA Brown (61.65±1.11) and lowest in Decalb White (52.58±4.21). Egg production percentages and egg weights varied significantly among 5 different hybrids. Mortality percentage did not vary significantly but feed consumption per birds per day varied significantly (P<0.05) among hybrids. Highest average feed consumption (g/bird/d) was observed in ISA Brown (113.18±1.94) and lowest in Decalb White (95.40±9.09). Correlation coefficient (r) indicates that egg weight increased with the increase of egg production. Among the five different commercial layer hybrids, Hisex White showed the best egg production performance and could be recommended for the farmers of Bangladesh. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> DOI: http://dx.doi.org/10.3329/bjas.v42i2.18491 <span style="font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">Bang. J. Anim. Sci. 2013. 42 (2): 114-122